2021
DOI: 10.1002/pbc.29005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations and outcomes of children with cancer and COVID‐19: A systematic review

Abstract: Information regarding the novel coronavirus disease (COVID‐19) in pediatric oncology is limited. We conducted a systematic review of the available published literature on children with cancer affected by COVID‐19. The last date of the study search was October 20, 2020, and 33 studies comprising 226 children were included for the final analysis. Data were extracted in a predefined data collection form, and the variables were extracted and analyzed. Patients with hematological malignancies were more in number. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 45 publications
3
79
2
4
Order By: Relevance
“…Cases of COVID-19 in children and adolescents with cancer have been reported worldwide. In the systematic review by Meena et al, 57 collecting data from 33 studies (18 case reports and 15 case series), 55, clinical and outcome of 226 children with cancer and COVID-19 were described: 53% of the patients were affected by hematological malignancies and 47% by solid tumors. The median age was seven years with a male to female ratio of 1.7:1; 34 patients were in intensive chemotherapy and 17 post-HSCT.…”
Section: Covid-19 In Children and Adolescents With Cancermentioning
confidence: 99%
“…Cases of COVID-19 in children and adolescents with cancer have been reported worldwide. In the systematic review by Meena et al, 57 collecting data from 33 studies (18 case reports and 15 case series), 55, clinical and outcome of 226 children with cancer and COVID-19 were described: 53% of the patients were affected by hematological malignancies and 47% by solid tumors. The median age was seven years with a male to female ratio of 1.7:1; 34 patients were in intensive chemotherapy and 17 post-HSCT.…”
Section: Covid-19 In Children and Adolescents With Cancermentioning
confidence: 99%
“…Children are generally at low risk for serious complications 1 ; children with cancer (CwC), however, are vulnerable to infections mainly due to immunosuppression caused by treatment. 2 We aimed to assess the magnitude and severity of COVID-19 among CwC in Greece.…”
Section: E T T E R T O T H E E D I T O R Covid-19 Among Children With Cancer In Greece (2020): Results From the Nationwide Registry Of Chmentioning
confidence: 99%
“…Children are generally at low risk for serious complications 1 ; children with cancer (CwC), however, are vulnerable to infections mainly due to immunosuppression caused by treatment. 2 We aimed to assess the magnitude and severity of COVID-19 among CwC in Greece.An electronic survey entailing demographic characteristics, cancer type, COVID-19 infection, treatment, and outcome information among…”
mentioning
confidence: 99%
“…Out of 15 deaths, four of them were not related to COVID-19. Thus, the mortality rate was 4.9% [33]. Millen et al reported 54 positive children of COVID-19 with cancer.…”
Section: Covid-19 Experience In Pediatric Oncologymentioning
confidence: 98%